2018
DOI: 10.5296/bms.v10i1.15003
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Internal Controls in Rural Community Banks: Evidence from Ghana

Abstract: Internal control is relevant in every business establishment, though its presence may not be a guarantee that fraud and corporate scandals would cease to occur. From the rural banking communities in Ghana, this study examines the significance of internal control element on the performance of elected rural banks. The statistical analysis and inferential judgment is based on the responses gathered from 650 bank employees on the functioning of internal controls.  Based on the quantitative results and analysis, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…Katushabe ( 2016) argues further that monitoring should be continuous in order to yield the desire results. Jianguo et al (2019) identified with this by observing that monitoring, like other control components requires consistency, persistency, and repetitiveness to achieve needed results. According to Bukenya and Kinatta (2012), the efficacy of the procedures put in place to trace ongoing monitoring determine the scope and frequency of monitoring required to achieve set organizational objectives in the control process.…”
Section: Review Of the Control Environmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Katushabe ( 2016) argues further that monitoring should be continuous in order to yield the desire results. Jianguo et al (2019) identified with this by observing that monitoring, like other control components requires consistency, persistency, and repetitiveness to achieve needed results. According to Bukenya and Kinatta (2012), the efficacy of the procedures put in place to trace ongoing monitoring determine the scope and frequency of monitoring required to achieve set organizational objectives in the control process.…”
Section: Review Of the Control Environmentmentioning
confidence: 99%
“…Katushabe (2016) observes that control activities include all activities that are put in place as part of internal controls by an organization to remove the element(s) of risk and thus reasonably assure achievement of organizational objectives. Jianguo et al (2019) complement this by adding that control activities include all the measures that are established to identify and address risk within an organization. According to Hayes et al (2014), control activities comprise a set of policies and processes set in motion by an organization to mitigate against the effect of risk and put an organization on a path towards sustained growth and development.…”
Section: Review Of Control Activitiesmentioning
confidence: 99%
See 1 more Smart Citation